Improved understanding of polar ozone chemistry and the future of the Antarctic ozone hole - Kremser, Stefanie (2011)
Coupled chemistry-climate models (CCMs) are currently the most appropriate tools for projecting the evolution of the ozone layer through the 21st century and its impact on climate. However, numerous sources of uncertainties in CCM projections of the stratospheric ozone layer were revealed in the past. In this thesis three sources of uncertainty were investigated: (i) uncertainties in the kinetic reaction rates of an important ozone depleting catalytic cycle, (ii) uncertainties resulting from different future greenhouse gas (GHG) emissions, and (iii) uncertainties in the representation of key chemical processes in CCMs. This thesis presents two methods to derived key kinetic reactions rates driving polar ozone depletion from atmospheric measurements, such as ground-based chlorine monoxide (ClO) measurements, thereby focussing on the kinetic reaction rates driving the effectiveness of the ClO dimer cycle during the day. The ClO dimer is one of the most destructive ozone loss processes in polar regions. The derived results are in agreement with previous studies and confirm that a rather higher value of the ratio of kinetic parameters J/kf (where J is the photolysis frequency and kf is the dimer formation rate) than currently recommended is required to explain the atmospheric measurements. The findings of this thesis highlight the need for long-term atmospheric measurements of day and night-time ClO and ClOOCl (referred to as the ClO dimer) and the need to investigate the kinetic reaction rates under stratospheric conditions. The uncertainty in the ozone projections that arises from the uncertainty in future emissions of GHGs has been subject to the second part of this thesis. A semi-empirical model approach which is used to investigate the evolution of stratospheric activated chlorine concentrations and related changes in Antarctic ozone depletion in a changing climate is presented. The sensitivity of the return dates of Antarctic ozone to historic levels (e.g. 1960 or 1980) to GHG emissions scenarios is examined. ...